2011
DOI: 10.1002/tox.20708
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biosensors for evaluating potential impacts of estrogenic endocrine disrupting compounds in multiple species

Abstract: To study the effects and possible mechanisms of suspected endocrine disrupting compounds (EDCs), a wide variety of assays have been developed. In this work, we generated engineered Escherichia coli biosensor strains that incorporate the ligand-binding domains (LBDs) of the β-subtype estrogen receptors (ERβ) from Solea solea (sole), and Sus scrofa (pig). These strains indicate the presence of ligands for these receptors by changes in growth phenotype, and can differentiate agonist from antagonist and give a rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…Initial studies used the human estrogen (ER␣) and thyroid hormone (TR␤-1) receptors and showed that this sensor can differentiate between receptor agonists and antagonists (71). Further, the modular design of the sensor has simplified the development of additional biosensors based on estrogen (ER␣ and ER␤) (69) and thyroid hormone (TR␣-1 and TR␤-1) receptors (72), as well as the human peroxisome proliferator-activated receptor ␥ (PPAR␥) receptor (73) and several animal estrogen receptors (74).…”
Section: Detecting Small Moleculesmentioning
confidence: 99%
“…Initial studies used the human estrogen (ER␣) and thyroid hormone (TR␤-1) receptors and showed that this sensor can differentiate between receptor agonists and antagonists (71). Further, the modular design of the sensor has simplified the development of additional biosensors based on estrogen (ER␣ and ER␤) (69) and thyroid hormone (TR␣-1 and TR␤-1) receptors (72), as well as the human peroxisome proliferator-activated receptor ␥ (PPAR␥) receptor (73) and several animal estrogen receptors (74).…”
Section: Detecting Small Moleculesmentioning
confidence: 99%
“…It could differentiate agonist from antagonist and give a rough indication of binding affi nity via dose-response curves. In tests the strains correctly identifi ed estrogenic test compounds, so it can be useful in initial comparative analysis of EDCs impacts across multiple species [16].…”
Section: Bacterial and Yeast Biosensors For Evaluating Potential Impamentioning
confidence: 99%
“…The biological activity of EDCs have been monitored by use of biomarkers such as vitellogenin, choliogenin and a DNA binding assay. Because of their diversity and simple nature, genetically engineered bioluminescent E. coli biosensors, which are sensitive to oxidative, DNA, membrane or protein damage, have been applied to EDCs screening and classifi cation [8,16]. Applications of reporter genes for screening of hormonal active compounds in the environment are broadly described and summarized by Svobodová and Cajthaml 2010 [41].…”
Section: Bacterial and Yeast Biosensors For Evaluating Potential Impamentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the binding of an appropriate ligand to the fused LBD activates a thymidylate synthase (TS) reporter enzyme, which allows the E. coli strain D1210DthyA expressing this protein to grow in media lacking thymine. This sensor is capable of differentiating agonist compounds from antagonist compounds and has shown utility in the identification and characterization of a number of compounds that bind to human and animal estrogen receptors (ERs; Gawrys et al 2009, Gierach et al 2013. More recently, this strategy has been validated for subtype-selective human TR ligands using a small library of known selective ligands (Gierach et al 2012).…”
Section: Introductionmentioning
confidence: 99%